2010
DOI: 10.1016/j.ijsu.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the use of glyceryl trinitrate ointment after haemorrhoidectomy as an analgesic and in promoting wound healing

Abstract: This meta-analysis has shown that GTN ointment used post-haemorrhoidectomy has a significant analgesic effect in the intermediate time period (ie. Days 3-7). It also significantly improved wound healing at 3 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 29 publications
0
36
3
Order By: Relevance
“…There are several forms of nitrates such as Nitroderm bands used after haemorrhoidectomy to reduce the IAS spasm; however, the ointment is the most commonly available and used form. Ratnasingham et al in their meta-analysis showed that the post-hemorrhoidectomy use of 0.2% GTN ointment was statistically significant in reducing post-operative pain on days 3 and 7, but not statistically significant in reducing pain on post-operative day 1, probably because the major contributor of pain in the early period post-operatively is due to the surgical trauma [10]. In our study, 0.4 % GTN ointment showed a significantly effect on post-operative pain reduction during the first week after surgery (4.1±1.8 vs 7.5±1.4, p<0.0001, expressed as mean VAS score).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several forms of nitrates such as Nitroderm bands used after haemorrhoidectomy to reduce the IAS spasm; however, the ointment is the most commonly available and used form. Ratnasingham et al in their meta-analysis showed that the post-hemorrhoidectomy use of 0.2% GTN ointment was statistically significant in reducing post-operative pain on days 3 and 7, but not statistically significant in reducing pain on post-operative day 1, probably because the major contributor of pain in the early period post-operatively is due to the surgical trauma [10]. In our study, 0.4 % GTN ointment showed a significantly effect on post-operative pain reduction during the first week after surgery (4.1±1.8 vs 7.5±1.4, p<0.0001, expressed as mean VAS score).…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis of Ratnasingham et al [10], on three studies, it has been shown that application of 0.2 % GTN ointment is associated with a significantly improved rate of wound healing at 3 weeks compared to matched placebo controls. A theory is that GTN may works in the same manner as in anal fissures, increasing the anodermal blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical diltiazem showed a marginal benefit in reducing pain after surgery [25][26][27]. Glyceryl trinitrate ointment improved wound healing and reduced postoperative pain [28]. A recent randomized trial confirmed these results [29].…”
Section: Complicationsmentioning
confidence: 96%
“…17 Research has also shown that GTN, as well as other anal spasmolytic agents, are helpful in reducing postoperative pain and healing time after open hemorrhoidectomy. [19][20][21] However, this benefit has not been explored in patients after stapled hemorrhoidectomy. The aim of this study was to conduct a randomized controlled trial comparing pain after stapled hemorrhoidectomy in patients with topical GTN and without (control patients) postoperatively.…”
mentioning
confidence: 99%